Civil and Military Integration in the Indonesian Defense Industry - Sukrisna, Cecep; Prihantoro, Mitro (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
A country with an established defense industry is considered to have a strategic advantage in the global or world order. The defense industry in Indonesia has a long history and has always been eager to empower and improve the national defense industry. At the same time, the defense industry has to face very tough rivals facing global competition that is not easy. With a qualitative approach, it is necessary to tactical and operational efforts of civilian-military integration following the development of a dynamic global military situation.